2016
DOI: 10.1166/jnn.2016.11328
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Preoperative Tattooing with Charcoal Nanoparticles for Laparoscopic Resection of Gastric Tumors

Abstract: Laparoscopic surgery has many benefits for dissection of gastrointestinal cancer. However, it is difficult to identify small lesions for early gastric cancer during laparoscopic surgery. In the present study efficacy of charcoal nanoparticles as a tattooing agent during laparoscopic surgery for gastrointestinal cancer was evaluated. Forty four patients undergoing laparoscopic surgery for gastric tumors were enrolled. Charcoal nanoparticles were injected preoperatively through an endoscope 3 h preoperatively. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Wang et al evaluated the imaging efficacy of charcoal nanoparticles during laparoscopic surgery for gastrointestinal cancer. 51 The nanoparticles served as a tattoo agent and located tumors within a short time. Subsequent pathologic examination revealed that tumors in all removed tissues, which indicated nanotechnology contributed to a precise removal of gastric cancer.…”
Section: Nanotechnology Approaching Gastric Cancermentioning
confidence: 99%
“…Wang et al evaluated the imaging efficacy of charcoal nanoparticles during laparoscopic surgery for gastrointestinal cancer. 51 The nanoparticles served as a tattoo agent and located tumors within a short time. Subsequent pathologic examination revealed that tumors in all removed tissues, which indicated nanotechnology contributed to a precise removal of gastric cancer.…”
Section: Nanotechnology Approaching Gastric Cancermentioning
confidence: 99%
“…Since 2013, based on the advantages and effectiveness of carbon nanoparticles (7), we carried out a new exploration of nanocarbon dyes in precision surgery for gastrointestinal (8,9), thyroid (10), and breast (11) tumors, providing a basis for finding a new and effective staining method. Furthermore, we previously conducted a retrospective analysis of the short-term follow-up of preoperative carbon nanoparticle staining in 16 breast cancer patients and also performed a preliminary study of carbon nanoparticle staining before neoadjuvant chemotherapy in 3 patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to identify small lesions in EGC during laparoscopic surgery even for a skilled surgeon. [ 8 ] Because EGCs do not involve the serosal layer, the location of a tumor cannot be determined by the laparoscopic view alone. [ 2 ] Without precise preoperative localization, a large portion of the stomach has to be dissected to ensure complete eradication of the cancer tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some patients still need subsequent surgical resections owing to positive resection margins. [ 8 ] Thus, correct identification of the tumor location is very important, especially for gastric cancer in the middle third of the stomach. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%